Chondritic breccias: An optical microscopic classification - Kimura, M.; Yamaguchi, A. (Polar Science, 2022)
Numerous meteorites are breccias, indicating asteroid collisions. Herein we systematically investigate brecciated chondrites to efficiently and quickly classify large numbers of breccias that are housed in organizations such as the National Institute of Polar Research (NIPR). We observed 1024 chondrites in the NIPR collection only by using optical microscopy. Many terms have been proposed to describe breccias. In order to classify breccias in a short time, we propose a determinative chart only by optical microscopy from terminology previously proposed and our observations. Fragmental breccias consist of primordial lithology as a clast or a host among fragmental fine-grained minerals. If the lithology is apparently consistent throughout, it is considered a monomict breccia. Otherwise, it is provisionally called a fragmental breccia. Breccias can be classified according to evidence of in situ melting. Melt breccias contain unmelted clasts, which preserve the original chondritic textures, whereas melt rocks do not contain such clasts and represent nearly total melting. journal article